2016
DOI: 10.1097/gox.0000000000000736
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Mine-Shrapnel and Gunshot Wound Closure Using Keystone Island Perforator Flaps

Abstract: Background:During military operations, one aspect of a plastic surgeon’s work is to restore extensive and deep wound defects in a short period of time and provide a high degree of functional recovery to the damaged area. Because many injuries caused by military operations cannot be closed using a primary suture, the specialist has to select another surgical approach to close the wound defect. Surgeons must select methods that not only cover the extensive wound defect in 1 step but also allow skin coverage that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…One article was a prospective cohort study; [ 7 ] all other included articles were case series. [ 5 , 6 , 8 13 ] The mean age of enrolled patients was 52.4 ± 6.4 years (range, 2–82 years), and the average follow-up duration was 15.3 ± 8.4 months.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One article was a prospective cohort study; [ 7 ] all other included articles were case series. [ 5 , 6 , 8 13 ] The mean age of enrolled patients was 52.4 ± 6.4 years (range, 2–82 years), and the average follow-up duration was 15.3 ± 8.4 months.…”
Section: Resultsmentioning
confidence: 99%
“…There were 2 articles reporting more than 1 keystone flap on the same patient. [ 10 , 13 ] Multiple keystone flaps on the same patient or on the same leg might affect the complication rate. Stone et al [ 10 ] reported 32 keystone flaps in 30 patients, with 2 patients having bilateral lower leg flaps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Short surgical times 36,37,42,50,55 without complex intrasurgical or postsurgical monitoring, a single operative field, and a more “stable” perfusion 50 are some of the additional advantages of KF that reduce morbidity, mortality, and intrahospital stay. 31,33 This differs from the microvascular options that require a wide learning curve and large resources for its execution.…”
Section: Discussionmentioning
confidence: 99%